Supporting employability through sport: what kind of training? - Gozzoli, Caterina; Palumbo, Martina; Zanoli, Edgardo (Frontiers in Sports and Active Living, 2023)
Training, as a core device in the projects that use sport to increase employability, is today a much-cited element in papers in the sector. However, there seems to be little research that specifically delves into training processes. This contribution analyses the state of the art on the subject, focusing on the characteristics of the training courses mentioned in literature, highlighting some recurring critical issues. A proposal, which considers the limitations discussed above, is formulated as a result of this analysis. More specifically, we introduce, as a contribution to the debate, a training model for team sports coaches developed within the EU Erasmus+ sport project SBSMED. Theoretical assumptions, methodology, contents and assessment methods of training effectiveness will be explained, highlighting valuable elements and the open issues that emerge from this experience.